ANALISIS EFEKTIVITAS SISTEM PENDAFTARAN ONLINE PASIEN RAWAT JALAN BERBASIS WEB PADA UPTD PUSKESMAS KERAMBITAN II KABUPATEN TABANAN - Ni Luh Putu Ratih Ariani (Health Care Media, 2022)
The patient registration place is one part of health services; currently patient registration at the UPTD Puskesmas Kerambitan II in Tabanan Regency is still done manually. The number of patient visits per week is 387 patients and officers need an average of 14 minutes to carry out the registration process. Whereas in the standard operating procedure set by the Puskesmas, it is allocated less than 10 minutes, thus causing queues build-up. The purpose of this study is to find out how effective the web-based outpatient online registration system is during outpatient registration. This type of research is quantitative research with Pre-Experimental Design as the research design and the system development method used in this research is the System Development Life Cycle (SDLC). The results of the study using the usability test obtained a percentage value of 80% which can be categorized as “Good”. The results of hypothesis testing using the Wilcoxon signed rank test obtained a significant value of 0.00, namely <0.05. Based on the conclusions of this study, it is stated that the use of a web-based outpatient online registration system is effective in reducing outpatient registration time.